The 2009 edition of the GEISA spectroscopic database - Jacquinet-Husson N.; Crepeau L.; Armante R.; Boutammine C.; Chédin A.; Scott N. A.; Crevoisier C.; Capelle V.; Boone C.; Poulet-Crovisier N.; Barbe A.; Campargue A.; et al. (2011, 2011)
Title screen